Bioequivalence studies of two different film-coated tablet formulations of valacyclovir of two different strengths in healthy volunteers - Rita, Neves; Susana, Almeida; Augusto, Filipe; Ana Cristina, Spinola Franco; Zohreh, Abolfathi; Ann, Lévesque; Jordi, Ortuño; Alex, Toms (Arzneimittelforschung, 2010)
These studies were conducted in order toassess the bioequivalence of two film-coated formulations containing 250 mg and 1000 mg of valacyclovir (INN: valaciclovir; CAS 124832-26-4), which is the L-valyl ester and a pro-drug of the antiviral drug acyclovir (INN: aciclovir). In the study with valacyclovir 250 mg, 36 healthy subjects were enrolled in arandomized, single-dose, open-label, 2-way crossover study, with a washout period of 10 days. In the study with valacyclovir 1000 mg, 46 healthy subjects were enrolled in a randomized, single-dose, open-label, 2-way crossover study, with a washout period of 7 days. Plasma samples were collected up to 36 h post-dose for both studies. Valacyclovir levels were determined byliquid chromatography with tandemmass detection (ie, the LC/MS/MS meth-od) (lower limit of quantification: 0.50 ng/mL for valacyclovir and 9.93 ng/mL foracyclovir for the 250 mg study and1.00 ng/mL for valacyclovir and 20.00 ng/mL for acyclovir for the 1000 mg study). Pharmacokinetic parameters used forbioequivalence assessment were the area under the concentration-time curve fromtime zero to time of last non-zero concentration (AUC0–t) and from time zero to infinity (AUC0–inf) and maximum observed concentration (Cmax). These parameters were determined from the valacyclovir concentration data usingnon-compartmental analysis. In the study with valacyclovir 250 mg formulations, the 90% confidence intervals obtained by analysis of variance (ANOVA) forvalacyclovir were 107.54–124.26% for Cmax, 95.45–103.46% for AUC0–inf and 95.53–103.63% for AUC0–t whereas foracyclovir the 90% confidence intervalsobtained were 103.19–117.02% for Cmax, 99.61 – 106.92% for AUC0–inf and 99.58–106.94% for AUC0–t. In the study with valacyclovir 1000 mg formulations, the 90% confidence intervals obtained forvalacyclovir were 93.20–107.35% for Cmax, 90.87–96.27% for AUC0–inf and 90.87–96.27% for AUC0–t whereas foracyclovir the 90% CIs obtained were 95.98–104.94% for Cmax, 97.13–103.94% for AUC0–inf and 97.14–104.09% for AUCo–t. All the 90% confidence intervals obtained for all the parameters assessed were within the predefined range (80–125%). Based on these results, it can be concluded that the evaluated formulation sare bioequivalent in terms of rate and extent of absorption.
Keywords: Antiviral drugs; CAS 124832-26-4Valacyclovir, bioequivalence